(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Mahatma Gandhi’s philosophy of Swadeshi emphasized economic self-reliance, decentralized industries, and rural empowerment. This study examines the relevance of Swadeshi in modern rural development, particularly through small-scale industries (SSIs). It explores how Gandhi’s vision countered colonial exploitation, revived indigenous industries, and promoted sustainable livelihoods. The research highlights contemporary rural development strategies, including government policies, technological advancements, and financial inclusion, that align with Swadeshi principles. Findings indicate that decentralized industrialization fosters employment, reduces rural-to-urban migration, and enhances socio-economic resilience. Additionally, eco-friendly practices and renewable energy integration in SSIs contribute to sustainable development. The study concludes that modernizing Swadeshi-based industries through technology, policy support, and financial assistance ensures inclusive and sustainable rural growth, making Gandhi’s vision highly relevant in today’s globalized economy.